Echocardiography-guided percutaneous intramyocardial alginate hydrogel implants for heart failure: canine models with 6-month outcomes - Ma, Hui; Gong, Wenqing; Lim, D. Scott; Li, Jing; Ta, Shengjun; Hu, Rui; Li, Xiaojuan; Zheng, Minjuan; Liu, Liwen (Frontiers in Cardiovascular Medicine, 2024)
Echocardiography-guided percutaneous intramyocardial alginate-hydrogel implantation (PIMAHI) is a novel treatment approach for heart failure (HF). We validated PIMAHI safety and efficacy in canine HF models.Methods: Fourteen canines with HF (produced by coronary artery ligation, left ventricular ejection fraction [LVEF] <35%) were randomised to PIMAHI treatment (n=8) or controls (n=6).Echocardiography, two-dimensional speckle tracking echocardiography, and pathological examinations after a 6-month follow-up were performed. Repeated-measures analysis of variance was used for within-group comparisons.: At 6-month follow-up, PIMAHI treatment reversed LV dilation and remodelling, increasing LV free wall thickness (LVFW, p=0.002) and interventricular septum thickness (IVS, p<0.001) and reducing LV end-diastolic volume (EDV, p=0.008) and end-systolic volume (ESV, p=0.004). PIMAHI significantly improved LV systolic function, increasing LVEF (EF, p=0.004); enhanced LV myocardial contractility, including increased LV global longitudinal strain (GLS, p<0.001), global circumferential strain (GCS, p=0.006), and mitral annulus displacement (MAD, p=0.001). Compared with controls at 6-month, PIMAHI group significantly increased LVFW thickness (8.5±0.3 vs. 6.8±0.2 mm, p=0.002) and IVS (7.9±0.1 vs. 6.1±0.2 mm, p<0.001); decreased LVEDV (30.1±1.6 vs. 38.9±4.5 mL, p=0.049 ) and ESV (17.3±1.2 vs. 28.7±3.6 mL, p=0.004); increased LV systolic function (42.7±1.5 vs 26.7±1.1% in EF, p=0.001); and enhanced LV myocardial contractility including GLS (13.5±0.8 vs 8.4±0.6%, p=0.002), GCS (16.5±1.4 vs 9.2±0.6%, p=0.001), and MAD (11.4±3.5vs 4.6±2.5 mm, p=0.003). During PIMAHI treatment, no sustained arrhythmia, pericardial, or pleural effusion occurred. Conclusions: PIMAHI in canine HF models was safe and effective. It reversed LV dilation and improved LV function.